RFID for libraries : a practical guide - Pandian, M. Paul.; ScienceDirect eBooks (Oxford : Chandos, 2010)
Many modern technologies give the impression that they somehow work by magic, particularly when they operate automatically. A technology called RFID (Radio Frequency Identification) has exactly this characteristic. This book helps the library & information community to understand RFID technology from a library perspective.
Introduction -- RFID for libraries -- RFID systems for libraries : a review -- RFID implementation in libraries -- RFID issues -- Future developments of RFID.
Includes bibliographical references and index.
Print version record.
Elsevier
Safari Books Online
Keywords: Technical services (Libraries); Radio frequency identification systems; Radio frequency identification systems -- Cost effectiveness; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Electronic books